Citrulline protects human retinal pigment epithelium from hydrogen peroxide and iron/ascorbate induced damages. Issue 10 (23rd April 2022) - Hassel, Chervin; Couchet, Morgane; Jacquemot, Nathalie; Blavignac, Christelle; Loï, Cécile; Moinard, Christophe; Cia, David
Abstract: Oxidative stress plays an important role in the ageing of the retina and in the pathogenesis of retinal diseases such as age‐related macular degeneration (ARMD). Hydrogen peroxide is a reactive oxygen species generated by the photo‐excited lipofuscin that accumulates during ageing in the retinal pigment epithelium (RPE), and the age‐related accumulation of lipofuscin is associated with ARMD. Iron also accumulates with age in the RPE that may contribute to ARMD as an important source of oxidative stress. The aim of this work was to investigate the effects of L‐Citrulline (CIT), a naturally occurring amino acid with known antioxidant properties, on oxidative stressed cultured RPE cells. Human RPE (ARPE‐19) cells were exposed to hydrogen peroxide (H2 O2 ) or iron/ascorbate (I/A) for 4 h, either in the presence of CIT or after 24 h of pretreatment. Here, we show that supplementation with CIT protects ARPE‐19 cells against H2 O2 and I/A. CIT improves cell metabolic activity, decreases ROS production, limits lipid peroxidation, reduces cell death and attenuates IL‐8 secretion. Our study evidences that CIT is able to protect human RPE cells from oxidative damage and suggests potential protective effect for the treatment of retinal diseases associated with oxidative stress.